Frequency Modulation of Recombination Radiation Emitted by an InAs/GaAs Heterostructure with InAs Quantum Dots under the Influence of an Acoustic Wave - Peleshchak, R.M.; Dan’kiv, O.O.; Kuzyk, O.V. (Ukrainian Journal of Physics, 2022)
We have developed a theoretical model that describes the process of frequency modulation of radiation emitted at the recombination transition between the ground states of an electron and a hole in the InAs/GaAs heterostructure with InAs/GaAs quantum dots, the modulation being induced by an acoustic wave. The character of the dependence of the frequency modulation amplitude on the acoustic wave frequency is determined.